2019
DOI: 10.1007/s12144-019-00567-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of within-session breaks in play on responsible gambling behaviour during sustained monetary losses

Abstract: Rapid, continuous gambling formats are associated with higher risks for gambling-related harm in terms of excessive monetary and time expenditure. The current study investigated the effect on gambling response latency and persistence, of a new form of within-game intervention that required players to actively engage in response inhibition via monitoring for stop signals. Seventyfour experienced electronic gaming machine gamblers, with a mean age of 35.28 years, were recruited to participate in a rapid, continu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Finally, one breaks in play study (14%) suggested mixed responsible gambling impact [94]. The authors found that a three-minute break did increase the response latency between rounds for EGM players in the face of consistent losses.…”
Section: Narrative Reviewmentioning
confidence: 97%
See 1 more Smart Citation
“…Finally, one breaks in play study (14%) suggested mixed responsible gambling impact [94]. The authors found that a three-minute break did increase the response latency between rounds for EGM players in the face of consistent losses.…”
Section: Narrative Reviewmentioning
confidence: 97%
“…Bartoš and Schimmack [32] constructed a z-curve on the original studies that were subjected to replication in the OSC, recovering an Observed Discovery Rate of . 94 [.46, .75]). The responsible product design literature has a greater tolerance for null results (or tests more true negatives), a slightly lower expected discovery rate (though the confidence intervals have considerable overlap), and a similar expected replicability rate.…”
Section: Replicability and Transparencymentioning
confidence: 99%
“…Evidence for the efficacy of mandatory breaks in real gambling is limited (Auer et al, 2019;Hopfgartner et al, 2021). Parke et al (2019) found that a mandatory break of 3 minutes did not reliably influence the number of rounds played. However, after a break, people overall initiated new rounds more slowly during a period of sustained losses, suggesting that breaks may reduce response speed.…”
Section: Pauses In Play: Do They Reduce Response Speed and Risky Choi...mentioning
confidence: 99%
“…Evidence for the efficacy of mandatory breaks in real gambling is limited (Auer et al, 2019;Hopfgartner et al, 2021). Parke et al (2019) found a mandatory break of 3 minutes did not reliably influence the number of rounds played. However, after a break, participants overall initiated new rounds more slowly during a period of sustained losses, suggesting that breaks may reduce response vigor.…”
Section: Pauses In Play: Do They Reduce Response Vigor and Risky Choi...mentioning
confidence: 99%